244 White and red sorghum as primary carbohydrate sources in extruded diets of felines. (5th December 2019) - Schaumburg, Patrick von; He, Fei; Mangian, Heather; Hoke, Jolene; Godoy, Maria R C de
Abstract: The human interest of ancient grains replacing modern carbohydrate sources has reached the pet food market, and there has been increased focus on corn- and wheat-free diets in pet foods. The objectives of this research were to evaluate the effect of dietary supplementation of white and red sorghum grains on the gastrointestinal health of felines through the determination of apparent total tract macronutrient digestibility (ATTD), fecal characteristics, fermentative end-products, microbiota, and how the sorghum grains compared against a traditionally corn-based diet. Three diets containing 30% corn (CO), 30% white sorghum (WS), or 30% red sorghum (RS) were formulated to meet or exceed the AAFCO (2017) nutritional requirements for felines. Nine male cats were randomly assigned to one of the 3 dietary treatments using a replicated 3x3 Latin square design. Experiment periods consisted of 14 days (10 days of diet adaption + 4 days of total, fresh collection). All diets were highly digested by cats, however, ATTD of dry matter was highest (P < 0.05) for RS (81.13%) and lowest for CO (78.28%), organic matter was greatest (P < 0.05) for RS (86.40%) and lowest for CO (84.15%), crude protein was similar amongst diets with a range of 84.52%-86.57%, acid hydrolyzed fat was similar amongst diets with a range of 91.36%–92.79%, and total dietary fiber was greatest (P < 0.05) in WS (55.96%) with CO being lowest (44.66%). Fecal pH (6.28–6.54) and most metabolites did not differ among diets (P > 0.05), except for phenol/indole concentrations that were significantly lower (P < 0.05) in cats fed RS (178.88 ug/g) compared to CO (240.34 ug/g). Overall, the data gathered suggest that dietary supplementation of WS and RS as carbohydrate sources were well tolerated by the cats. Thus, sorghum is an acceptable alternative to corn in extruded diets of felines.